Clean energy - Beijing di tan qing jie neng yuan yan jiu yuan (Oxford University Press, 2017)
Clean Energy provides a high profile platform for scientists, academic researchers, engineers and industrial professionals to publish papers of the highest quality and significance in all areas of clean energy. Submissions will be blind reviewed and accepted papers will be published first online and paginated into the issue quarterly in both print and online versions.
Keywords: Clean energy : Periodicals; Energy industries : Periodicals; Renewable energy sources : Periodicals; Carbon dioxide mitigation : Periodicals; Green technology : Periodicals; Énergies propres : Périodiques; Industries énergétiques : Périodiques; Énergies renouvelables : Périodiques; Gaz carbonique : Réduction : Périodiques; Technologie de protection de l'environnement : Périodiques; Carbon dioxide mitigation; Clean energy; Energy industries; Green technology; Renewable energy sources